The mediating role of trust to managers on the relationship between corporate reputation practices and employees' course of actions to customers - Erkmen, Turhan; Esen, Emel (EMERALD GROUP PUBLISHING LTD, 2014)
Purpose - The purpose of this study is to examine the role of trust to managers on the relationship between corporate reputation practices and employees' course of actions to customers in airline sector. Design/methodology/approach - A research questionnaire which measures corporate reputation, trust to managers and employees' course of actions to customers was designed by the researchers. Three hundred forty-three employees who are working in nine different companies in an airline sector have participated in the research. Findings - According to the results of the study, corporate reputation practices and trust to managers have an effect on employees' course of actions to customers; also trust to managers does not have any mediating role between these variables. Research limitations/implications - As this study is conducted in airline companies, we cannot generalize the results to the companies in other sectors. In addition, during the application of questionnaires, some participants found the questionnaire too long and they withdrew. This yielded to a lower participation rate. Practical implications - The findings of the study may get the board of directors' or managers' attention to the point that they should become aware of the importance of corporate reputation, corporate social responsibility, employees' behaviors and trust in their organizations. Originality/value - This study aims to make several contributions to the marketing and management literature. Firstly, it extends the recent marketing and management literature on corporate reputation by examining trust to managers and employees' behaviors.
Keywords: Corporate social responsibility; Corporate reputation; Employees' course of actions to customers; Trust to managers; ORGANIZATIONAL TRUST; INTERPERSONAL-TRUST; COMMITMENT; BEHAVIOR; Business & Economics